2021
DOI: 10.1038/s41586-021-03536-w
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibition of METTL3 as a strategy against myeloid leukaemia

Abstract: The N6-methyladenosine (m 6 A) is an abundant internal RNA modification 1,2 catalysed predominantly by the METTL3-METTL14 methyltransferase complex 3,4 . The m 6 A writer METTL3 has been linked to the initiation and maintenance of acute myeloid leukaemia (AML), but its true therapeutic importance is still unknown [5][6][7] . Here we present the identification and characterisation of a highly potent and selective first-in-class catalytic inhibitor of METTL3 (STM2457) and its co-crystal structure bound to METTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
568
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 787 publications
(586 citation statements)
references
References 48 publications
15
568
2
1
Order By: Relevance
“…Indeed, there was good agreement between sites detected using this DRS approach and peak regions identified by meRIP-seq for polyadenylated RNAs isolated from human adenovirus type 5 (Ad5)-infected cells. To test whether DRS could effectively detect m 6 A installation on β-coronavirus RNAs, cells were infected with SARS-CoV-2 (A549 +ACE2 ) or HCoV-OC43 (MRC-5) under the same conditions used for meRIP-seq in the presence of STM2457, a new and highly selective small molecule inhibitor of METTL3 activity (Yankova et al 2021), or a structurally related control compound STM2120 that is >3000-fold less potent as an METTL3 inhibitor as measured by in vitro methylation assay (Supplemental Fig. S6).…”
Section: β-Coronavirus Rnas Are M 6 A-modifiedmentioning
confidence: 99%
“…Indeed, there was good agreement between sites detected using this DRS approach and peak regions identified by meRIP-seq for polyadenylated RNAs isolated from human adenovirus type 5 (Ad5)-infected cells. To test whether DRS could effectively detect m 6 A installation on β-coronavirus RNAs, cells were infected with SARS-CoV-2 (A549 +ACE2 ) or HCoV-OC43 (MRC-5) under the same conditions used for meRIP-seq in the presence of STM2457, a new and highly selective small molecule inhibitor of METTL3 activity (Yankova et al 2021), or a structurally related control compound STM2120 that is >3000-fold less potent as an METTL3 inhibitor as measured by in vitro methylation assay (Supplemental Fig. S6).…”
Section: β-Coronavirus Rnas Are M 6 A-modifiedmentioning
confidence: 99%
“…Indeed, small molecule ligands for METTL3 writer complex [ 116 ], FTO [ 170 ], and ALKBH5 [ 171 ] erasers have already been described by the members of the IHD-EPITRAN Consortium. Remarkably, just recently, a potent METTL3 inhibitor has also been reported with leukemia-repressing effects in vivo in mice, providing simultaneously an enchanting proof-of-principle and a seminal endeavor to thrust the door ajar into the yet uncharted realm of epitranscriptomics-based pharmacology in vivo—ultimately shifting eyes also increasingly towards the clinic [ 172 ]. Hence, both the existing and future breakthroughs regarding epitranscriptomic pharmacology is closely monitored and implemented accordingly to the mid/late phases of the IHD-EPITRAN study as a further applicatory dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Eliza et al, 2021 [ 48 ] have discovered the selective inhibitor of Mettl3 and Mettl14 (STM2457, IC50 = 16.9 nM) in controlling AML via high-throughput screening of 250,000 drug-like compounds. Functionally, authors showed a significant effect of STM2457 in reducing clonogenic potential and inducing apoptosis in human and mouse AML model without affecting normal human cord blood (CD34 + /HSPCs) and non-leukaemia (HPC7) hematopoietic cells [ 48 ]. Moreover, in vivo studies on AML patient-derived xenograft (PDX) model and primary murine MLL-AF9/Flt3 ltd/+ model showed convincing anti-leukaemia effect of STM2120 inhibitors [ 48 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Functionally, authors showed a significant effect of STM2457 in reducing clonogenic potential and inducing apoptosis in human and mouse AML model without affecting normal human cord blood (CD34 + /HSPCs) and non-leukaemia (HPC7) hematopoietic cells [ 48 ]. Moreover, in vivo studies on AML patient-derived xenograft (PDX) model and primary murine MLL-AF9/Flt3 ltd/+ model showed convincing anti-leukaemia effect of STM2120 inhibitors [ 48 ]. Similar findings have been reported from other research groups summarised in Table 3 [ 6 , 45 , 47 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%